2018
DOI: 10.1021/acs.inorgchem.8b01182
|View full text |Cite
|
Sign up to set email alerts
|

Equation of State and Amorphization of Ca9R(VO4)7 (R = La, Nd, Gd): A Combined High-Pressure X-ray Diffraction and Raman Spectroscopy Study

Abstract: Ca9R­(VO4)7 (R = rare earth) multicomponent oxides of a whitlockite-related structure are under consideration for applications in optoelectronics. In this work, the Czochralski-grown Ca9R­(VO4)7 crystals were investigated as a function of pressure by powder X-ray diffraction and single-crystal Raman spectroscopy. The diffraction experiments were performed at the ALBA synchrotron under pressures ranging up to 9.22(5), 10.7(1), and 8.55(5) GPa for R = La, Nd, and Gd, respectively, to determine the third order eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(128 reference statements)
1
2
0
Order By: Relevance
“…As discussed in the next paragraph, the bulk modulus at zero pressure ( B 0 ) and its pressure derivative () agree within confidence ellipses with the values obtained from the second-order EOS. The B 0 obtained is close to the bulk moduli found for other calcium compounds with the whitlockite-related structure, such as Ca 9 R(VO 4 ) 7 (R = La, Nd, Gd) 19 and β-Ca 3 P 2 O 8. 67,68 The reported bulk modulus for the low-pressure trigonal Ca 3 V 2 O 8 phase is much smaller that of other orthovanadates with similar chemical formulae, for example: Mn 3 V 2 O 8 , Co 3 V 2 O 8 , Ni 3 V 2 O 8 , and Zn 3 V 2 O 8 , however these compounds have different crystal structures which have been recently systematically studied.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…As discussed in the next paragraph, the bulk modulus at zero pressure ( B 0 ) and its pressure derivative () agree within confidence ellipses with the values obtained from the second-order EOS. The B 0 obtained is close to the bulk moduli found for other calcium compounds with the whitlockite-related structure, such as Ca 9 R(VO 4 ) 7 (R = La, Nd, Gd) 19 and β-Ca 3 P 2 O 8. 67,68 The reported bulk modulus for the low-pressure trigonal Ca 3 V 2 O 8 phase is much smaller that of other orthovanadates with similar chemical formulae, for example: Mn 3 V 2 O 8 , Co 3 V 2 O 8 , Ni 3 V 2 O 8 , and Zn 3 V 2 O 8 , however these compounds have different crystal structures which have been recently systematically studied.…”
Section: Resultssupporting
confidence: 83%
“…18 One Raman study on the related compound Ca 9−x R(VO 4 ) 7 (R = La, Nd, Gd) reported signs of partial amorphization around 9-10 GPa. 19 According to the results summarized above, the HP behavior of Ca 3 V 2 O 8 is different from that of other orthovanadates with equivalent chemical formulae. For instance, Zn 3 V 2 O 8 , Ni 3 V 2 O 8 , and Ba 3 V 2 O 8 remain stable up to at least 15, 20 23 21 and 29 GPa 22 respectively.…”
Section: Introductionmentioning
confidence: 97%
“…delafossite-type vanadates (e.g. LiVO2) [176], and metavanadates (e. g. Ca3(VO4)2 [177]). All these compounds have practical applications and his study under compression could lead to important discoveries.…”
Section: Future Perspectivesmentioning
confidence: 99%